Social Health Security Program and Poor: A Case Study of Dhangadhi Sub-Metropolitan City - Pandey, Ruku (Patan Prospective Journal, 2022)
It is a well-known fact that Alma Ata Conference on Primary Health Care held in Kazakhstan in 1978 called for all the countries to implement primary health care for increasing health care access to all the people at affordable cost and achieving the targets of "Health for All" by the year 2000.The conference had also emphasized the provision of preventive, promotive, curative, and rehabilitative services up to the community level for addressing main health problems (Gilllam, 2008). The World Health Organization also affirms that: “The enjoyment of the highest attainable standard of health is one of the fundamental rights of every human being without distinction of race, religion, political belief, economic or social condition” To ensure these rights to its citizens, every state has to invest organizational, human and financial resources to its optimum level.